Proceedings of the Seventh International Workshop on Data Mining for Online Advertising 2013
DOI: 10.1145/2501040.2501979
|View full text |Cite
|
Sign up to set email alerts
|

Real time bid optimization with smooth budget delivery in online advertising

Abstract: Today, billions of display ad impressions are purchased on a daily basis through a public auction hosted by real time bidding (RTB) exchanges. A decision has to be made for advertisers to submit a bid for each selected RTB ad request in milliseconds. Restricted by the budget, the goal is to buy a set of ad impressions to reach as many targeted users as possible. A desired action (conversion), advertiser specific, includes purchasing a product, filling out a form, signing up for emails, etc. In addition, advert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 23 publications
(28 reference statements)
0
82
0
1
Order By: Relevance
“…As a new advertising paradigm, other problems in RTB have also been studied. In [25] the authors focus on the pacing problem, where the target is to smoothly deliver the campaign budget. From the SSP perspective, the reserve price setting in RTB ad auctions is studied in [36].…”
Section: Notation Descriptionmentioning
confidence: 99%
“…As a new advertising paradigm, other problems in RTB have also been studied. In [25] the authors focus on the pacing problem, where the target is to smoothly deliver the campaign budget. From the SSP perspective, the reserve price setting in RTB ad auctions is studied in [36].…”
Section: Notation Descriptionmentioning
confidence: 99%
“…In our case, we model the bidding environment with respect to the cost and CPC as shown in Eq. (16), where X is a 2 × 2 matrix and b is a 2 × 1 matrix. After we obtain the expected ∆cost and ∆CPC from the feedback, we could adjust p and q by solving the equation in Eq.…”
Section: Multivariable Controlmentioning
confidence: 99%
“…Pérez-Gladish et al (2010) suggested linear logistical models in the field of advertising with the function of efficiency-maximization of a general amount of sales. Studies by K. C. Lee et al (2013) and C. Karande et al (2013) are focused on optimization of costs in the internet-advertising environment. Logistical models which ignore limitations on production capacities, possible efficiency of each separate type of advertising, amount of covering the target audience of potential consumers, minimal necessary volumes of using certain sources of advertising and a set of other factors have been suggested.…”
Section: Literature Reviewmentioning
confidence: 99%